(untitled) (Scientific journal of the Fergana State University, 2023)
In this article process of mining and metallurgy in Turkestan in the late XIX - early XX centuries is described. During this period, as a result of being controlled by the Russian protectorate, various types of citizens, scientists, industrialists, entrepreneurs came from the Russian Empire and studied their both underground and surface mineral resources.